Identification of new avian Infectious Bronchitis virus variants in Iranian poultry flocks by High Resolution Melting curve analysis - MASOUDIAN, A.; SHEIKHI, N.; BOZORGMEHRI-FARD, M. H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Avian Infectious bronchitis (IB) is a common coronavirus infection of chickens and responsible for performance reduction and increasing mortality due to subsequent respiratory, renal and/or reproductive disorders. Classification of causative agent is necessary to plan successful vaccination strategies to prevent the infection due to poor inter-strains cross-reaction. To identify dominant circulating strains in Iran, a Real-time PCR combined with 3’ Un-Translated Region (3’ UTR) High Resolution Melting (HRM) analysis designed as a rapid and reliable method for IB Virus (IBV) detection and differentiation. Samples collected from 20-suspected flocks and after PCR products, HRM curves of samples as well as 6 commercial IB live vaccines with 2 standard strains, were analyzed as references. IBV genomes detected in 11 samples while according to HRM analysis and calculating Genotype Confidence Percentage (GCP), 6 positive specimens identified as 793/B field strains and the left 5 found as new IBV variant strains. Then obtained PCR products sent for nucleotide sequencing to determine genotype relativity. All five infectious agents, related to QX-like type and indicating circulation of new variants in Iran as a probable cause of vaccination failures and consequent economical losses.